Potentiality of socio-educational study programmes’ improvement at Lithuanian universities - Alifanovienė, Daiva (Social Welfare: Interdisciplinary Approach, 2011)
The article deals with the attitude of the students of socio-educational (social education/work) study programmes of different Lithuanian universities towards their chosen study programmes in the aspects of subject blocks, modules and practical placements. In order to identify the students’ assessments the written questionnaire survey (Jankauskaitė, 2009) has been applied, using the half-closed type questionnaire. The survey was attended by Bachelor students of socioeducational (social education/work) study programmes of Lithuanian universities (N=193).